Individual- and community-level correlates of intermittent preventive treatment of malaria in pregnancy in Ghana: further analysis of the 2019 Malaria Indicator Survey - Jacob Owusu Sarfo; Patience Fakornam Doe; Dickson Okoree Mireku (Research in Health Services & Regions)
Abstract Background Ghana adopted the policy on Intermittent Preventive Treatment of malaria in pregnancy using Sulfadoxine-Pyrimethamine (IPTp-SP) in 2004. Notwithstanding the government’s and other stakeholders’ efforts in Ghana, optimal uptake (three or more doses of IPTp-SP) has slightly declined since 2016. The study examined the individual and community-level correlates of pregnant women who take optimal or none/partial doses (less than three doses) of IPTp-SP using the Ghana Malaria Indicator Survey (GMIS) 2019. Methods We conducted a secondary analysis of the GMIS 2019 data. Our analytical sample included 1,151 women aged 15-49 with their most recent birth in the last two years before the survey. Results The overall uptake among participants was approximately 8.2% for none, 30.15% for 1–2 (partial), and 61.6% for 3 or more (optimal) doses of IPTp-SP. The level of uptake differs depending on the individual rather than community-level characteristics of pregnant women. Individual-level demographic factors— residents in Upper East (OR 3.0, 95% CI; 1.2–7.3) and Upper West (OR 5.3, 95% CI; 1.9–14.7) —and health-related factors—the four or more antenatal (ANC) visits (OR 3.3, 95% CI; 1.8–6.0) were associated with optimal IPTp-SP uptake among pregnant women in Ghana. However, late scheduling of the first ANC visit in the second trimester (OR 0.7, 95% CI; 0.5–1.0)— predicted less IPTp-SP uptake. Conclusions Few regions (Upper East and West) are doing better than the capital, Greater Accra Region, in terms of optimal uptake. Also, early scheduling of ANC in the first trimester and increased ANC attendance are key for increased uptake. There is a need for policy, interventions, and research on malaria prevention in pregnancy to improve the decline in uptake.